Prevalence of hypothermia in elderly patients undergoing hip arthroplasty (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objectives: To determine prevalence of hypothermia in elderly patients undergoing hip arthroplasty Methods: A prospective, cross-sectional descriptive study was conducted. Tympanic thermometers were used to measure body temperature in patients aged 60 years and older who underwent hip arthroplasty under general endotracheal anesthesia at the Department of Anesthesiology, Cho Ray Hospital, from December 2022 to December 2023. Body temperature was measured at the following time points: pre-anesthesia, induction, and 10, 30, 60, and 90 minutes after induction, as well as at the end of surgery.Results: The incidence of hypothermia in hip arthroplasty surgery in elderly patients was 38.67%. Mild hypothermia was the most common (25.3%), followed by moderate hypothermia (13.3%), with no cases of severe hypothermia reported.Conclusion: Hypothermia in hip arthroplasty among elderly patients has a relatively high incidence, accounting for more than a quarter of cases. Strict temperature monitoring and appropriate preventive measures are crucial to reducing perioperative risks.